Corporate Ethics and Compliance Programs: A Report, Analysis and Critique - Weber, James; Wasieleski, David M. (2013)
This research reports on the current state of ethics and compliance programs among business organizations in the United States. Members of the Ethics and Compliance Officers Association (ECOA), the premier professional association for managers working in this field, were asked to provide in-depth responses to a series of questions covering various elements of their corporate ethics and compliance programs. The findings from this analysis indicate that ethics and compliance programs have multiple components that are implemented developmentally, are influenced by regulatory and legal efforts and have evolved into more sophisticated approaches that include risk assessment and employee performance appraisal. However, these programs remain vulnerable to sufficient resource allocation by the organization to be fully effective.
Keywords: Regulation; ethics programs; Compliance